Одговорите на менаџментот на предизвиците во е-трговијата во Република Македонија: случај на сајт за групно купување преку дневни зделки – grouper.mk - Ангеловска, Нина (Економски факултет, УКИМ, Скопје, 2016)
The rapid technological world poses numerous challenges for e-commerce companies and companies that aim to achieve growth and competitive advantage. A key success factor for any company is to adapt its strategy to the new technological trends. In this respect the aim of the dissertation is through complete analysis of the responses of the challenges that stand before e-commerce companies to help all participants in e-commerce and to give guidelines for successful management and better marketing decision making. Researches in the paper are conducted on the case of Grouper.mk, the first Macedonian group buying web site that revolutionized the e-commerce market in the country. The group-buying site represents an intermediary that offers promotional deals with discounts for end users in the form of coupons in cooperation with merchants whose products and services are promoted. The key challenges that are subject of analysis are: gamification as a means for achieving business goals; customer retention through efficient customer complaints management; and following trends expressed through evaluation of the influence of Grouper’s Mobile App and Facebook Ads, as a key prerequisite for growth and development. The last challenge that stands for every company is creating satisfied and loyal partners and end-users. This challenge represents an indicator for the successful management of the company as a whole and the appropriate responses to the given challenges and thus forms a comprehensive topic. We collect data throught surveys, interviews, case studies and mystery shopping, as well as internal data from Grouper’s database in order to conduct the researches in this dissertation. Throught application of various statistical tests, descriptive statistics, regression, structural equation modeling (SEM), factor analysis and other methods we depict a comprehensive view for the repsponses to the challenges that stand before the modern companies in the online world.
Management responses to e-commerce challenges in the Republic of Macedonia: case of group buying site by daily deals – grouper.mk
Докторска дисертација одбранета во 2016 година на Економскиот факултет во Скопје, под менторство на проф. д–р Сашо Јосимовски.
Keywords: group buying, daily deals, gamification, ROI, e-commerce, Grouper, intermediary, merchant, end-user, satisfaction, Republic of Macedonia